2019
DOI: 10.1111/cod.13246
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocyte phenotype of contact‐allergic patients: experience with nickel and p‐phenylenediamine

Abstract: Background: There is considerable interest in understanding the immunological variables that have the greatest influence on the effectiveness of sensitization by contact allergens, particularly in the context of developing new paradigms for risk assessment of novel compounds.Objectives: To examine the relationship between patch test score for three different contact allergens and the characteristics of T cell responses.Methods: A total of 192 patients with confirmed nickel, p-phenylenediamine (PPD) or methylis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…All chemical concentrations are listed in Table S2 (Supplementary Material) . Protein-conjugated chemicals (i.e., PPD- and MI-HSA) induced a comparable or even better proliferative response compared to the soluble correspondent chemical ( Supplementary Material, Table S2 ) (Jenkinson, 2010; Oakes, 2017; Popple, 2016; Wicks, 2019) [ 79 , 100 , 102 , 116 ]. Jenkinson and colleagues (2010) [ 79 ] calculated the equivalent molar scale of soluble and HSA-associated PPD to compare the strength of induced activation/proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All chemical concentrations are listed in Table S2 (Supplementary Material) . Protein-conjugated chemicals (i.e., PPD- and MI-HSA) induced a comparable or even better proliferative response compared to the soluble correspondent chemical ( Supplementary Material, Table S2 ) (Jenkinson, 2010; Oakes, 2017; Popple, 2016; Wicks, 2019) [ 79 , 100 , 102 , 116 ]. Jenkinson and colleagues (2010) [ 79 ] calculated the equivalent molar scale of soluble and HSA-associated PPD to compare the strength of induced activation/proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…They revealed that HSA-bound PPD possesses a stronger antigenic capacity. In the case of the protein-bound forms of the chemicals, the induced proliferative responses follow the classical dose-dependent trend and better correlate to patients’ patch test results (Popple, 2016; Wicks, 2019) [ 102 , 116 ]. Soluble chemicals generally become toxic at higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations